2014
DOI: 10.1097/hjh.0000000000000143
|View full text |Cite
|
Sign up to set email alerts
|

Salusin-β in rostral ventrolateral medulla increases sympathetic outflow and blood pressure via superoxide anions in hypertensive rats

Abstract: Salusin-β in the RVLM increases sympathetic outflow, blood pressure and heart rate via NAD(P)H oxidase-derived superoxide anions in renovascular hypertensive rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…8 Previous studies in our lab have shown that central salusin- β contributes to sympathetic activation, arginine vasopressin release and hypertension. 9, 10, 11 Salusin- β promotes proliferation of vascular smooth muscle cells (VSMCs) and vascular fibrosis. 12 ROS production in VSMCs mediates salusin- β -induced foam cell formation and monocyte adhesion, 13 VSMCs migration and intimal hyperplasia after vascular injury.…”
mentioning
confidence: 99%
“…8 Previous studies in our lab have shown that central salusin- β contributes to sympathetic activation, arginine vasopressin release and hypertension. 9, 10, 11 Salusin- β promotes proliferation of vascular smooth muscle cells (VSMCs) and vascular fibrosis. 12 ROS production in VSMCs mediates salusin- β -induced foam cell formation and monocyte adhesion, 13 VSMCs migration and intimal hyperplasia after vascular injury.…”
mentioning
confidence: 99%
“…Surgery for blood pressure recording was carried out under anesthesia with intraperitoneal injection of urethane (800 mg/kg) and achloralose (40 mg/kg). The depth of anesthesia was determined by the absence of corneal reflexes and paw withdrawal response to a noxious pinch [11]. At the end of the experiment, the rats were euthanized with an overdose of pentobarbital sodium (150 mg/kg, iv).…”
Section: Animalsmentioning
confidence: 99%
“…The rats were warmed for 10-20 min at 28°C before the measurements in order to allow detection of tail artery pulsations and to achieve the steady pulse level. SBP was obtained by averaging 10 measurements [11,20]. Mean arterial pressure (MAP) and heart rate (HR) were recorded under anesthesia with intraperitoneal injection of urethane (800 mg/kg) and a-chloralose (40 mg/kg).…”
Section: Measurement Of Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the sympathetic activity of obese rats (4,24), renovascular hypertensive rats (5,25,26) and SHRs (6,27,28) is enhanced compared with normotensive rats. Hexamethonium is a ganglionic blocker (10,11) and reduces blood pressure in SHR and Wistar rats (8).…”
Section: A B Cmentioning
confidence: 99%